Experimental production of arachnoiditis with glove powder contamination during myelography. - Williams, A G; Seigel, R S; Kornfeld, M; Whorton, J A (American Journal of Neuroradiology, 1982)
Adhesive spinal arachnoiditis is a rare condition of several causes, including complications of myelography. An experiment was conducted to study the effects of surgical glove powder contamination in the cerebrospinal fluid. The subarachnoid space of 45 rabbits was injected with either a suspension of powder from sterile surgical gloves, Pantopaque (iophendylate), or a combination of the two agents. Mild to severe arachnoiditis was produced in 10 of 17 animals injected with the combination of powder and Pantopaque. Only two of 16 rabbits injected with glove powder and one of nine with Pantopaque had more than minimal changes of arachnoiditis. Three rabbits (two injected with glove powder alone and one with both agents) died of meningitis within 1 week of injection. The combination of glove powder and Pantopaque is synergistic in producing arachnoiditis. These results emphasize the importance of meticulous technique in myelography.